2022
DOI: 10.1121/10.0015024
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of vowel clarity in the spectrotemporal modulation domain: Application to speech impairment evaluation

Abstract: This article reports on vowel clarity metrics based on spectrotemporal modulations of speech signals. Motivated by previous findings on the relevance of modulation-based metrics for speech intelligibility assessment and pathology classification, the current study used factor analysis to identify regions within a bi-dimensional modulation space, the magnitude power spectrum, as in Elliott and Theunissen [(2009). PLoS Comput. Biol. 5(3), e1000302] by relating them to a set of conventional acoustic metrics of vow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The data detailed here represent a subset of a larger project. Other components of the project have been published elsewhere: a speech perception in noise task and structural imaging data (T1w and diffusion MRI data) (Perron et al, 2021;Perron et al, 2022) and a standardized passage reading task (Marczyk, Belley, et al, 2022;Marczyk, O'Brien, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The data detailed here represent a subset of a larger project. Other components of the project have been published elsewhere: a speech perception in noise task and structural imaging data (T1w and diffusion MRI data) (Perron et al, 2021;Perron et al, 2022) and a standardized passage reading task (Marczyk, Belley, et al, 2022;Marczyk, O'Brien, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Spectral modulations characterise changes across frequency bands, having been shown to correspond with F0 ŕuctuations, harmonics, and formant patterns (Giraud and Poeppel, 2012;Rosen et al, 1992) with a perceptual upper limit around 3 cycles per octave (hereafter, c/o) (Dusan, 2007;Liu and Eddins, 2008) and a critical region of 0.8-1.3 c/o (Flinker et al, 2019). Numerous studies focused on unpacking the modulation representation of speech signals in the context of assessing speech intelligibility (Elhilali et al, 2003;Elliott and Theunissen, 2009;Flinker et al, 2019) and voice pathologies (Moro-Velázquez et al, 2015;Marczyk et al, 2022). Recent work by Ludusan and Wagner (2020b,a) showed that modulations of the amplitude envelope and F0 could be used to distinguish speech, laughter, and speech-laughter.…”
Section: Laughter Acoustics: Mimicry and Arousalmentioning
confidence: 99%
“…To obtain the MPS of laughs in our dataset, similar procedures described in Marczyk et al (2022) and were developed and applied. All processing was done in MATLAB 2021a (MathWorks Inc, USA) and based on adaptations to scripts described in Flinker et al (2019).…”
Section: Modulation Power Spectrummentioning
confidence: 99%
“…Spectral modulations have been shown to correspond with F0 fluctuations, harmonics, and formant patterns (Giraud & Poeppel, 2012;Rosen, Carlyon, Darwin, & Russell, 1992) with perceptual limits around 3 cycles per octave (hereafter, c/o) (Dusan, 2007;Liu & Eddins, 2008) and a critical region of 0.8-1.3 c/o (Flinker et al, 2019). Numerous studies focused on unpacking the modulation representation of speech signals in the context of assessing speech intelligibility (Elhilali, Chi, & Shamma, 2003;Elliott & Theunissen, 2009;Flinker et al, 2019) and voice pathologies (Moro-Velázquez, Gómez-García, Godino Llorente, & Andrade-Miranda, 2015;Marczyk, O'Brien, Tremblay, Woisard, & Ghio, 2022). There have been but a handful of studies that use STM metrics to analyze anything other than speech.…”
Section: The Acoustics Of Laughtermentioning
confidence: 99%